Case report: Cholesterol granuloma of femur - Hao, Shenshen; Dong, Shengli; Li, Hongke; Liu, Shuai; Chen, Honglei; Zhang, Zhifang (Frontiers in Surgery, 2022)
Background: Cholesterol granuloma (CG) is a particular type of granulation tissue reaction. It is a very rare benign lesion characterized by swelling growth due to a large number of cholesterol crystals and foreign body giant cells. There has been no report of a CG of the femur. Case presentation: A 74-year-old woman suffered from pain and discomfort in the upper right knee for 10 years, which became aggravated for 10 days. She was diagnosed with CG of the right femur at our hospital and was treated with surgery. During the operation, a large amount of yellow-brown, oily, crystal structures was found. Postoperative pathology investigations confirmed the lesion as a CG. Postoperative follow-up was carried out for 15 months that confirmed the effect of treatment was satisfactory. Conclusions: CG of the femur is an extremely rare benign lesion. Surgical treatment can provide effective treatment results.